Comparison of growth parameters of 40 varieties/clones short rotation coppice willow (Salix) - Bako, Attila; Tóthová, Diana (Acta Agraria Debreceniensis, 2011)
The plantation of willow varieties was established in 2009. The 40 different varieties and clones of Salix were planted at a research field in Kolíňany (Nitra district). The paper evaluates results from the first growing season in 2009. The survival rate of planted cuttings ranged from 55.56 % to 100.00 % after the first year. The lowest survival rate was reached by Terra Nova variety. The stem numbers per plant ranged from 1.17 ±0.37 to 2.53 ±0.98. The average height of one-year old stem varied from 65.82 ±36.60 cm to 225.58 ±68.61 cm. The average stem diameter ranged from 6.90 ±2.63 mm to 14.34 ±3.39 mm. There were statistically very significant differences in parameters of stem height stem diameter and stem numbers per plant among studied varieties/clones. The statistic method used was analysis of variance ANOVA. The varieties were then divided into 6 groups according to their similarity in observed parameters after the first growing season by cluster analysis. The best results were reached by varieties/clones classified in the second group. The survival rate, stem diameter and stem height values of these varieties/clones were above average.